2015
DOI: 10.1371/journal.pone.0134609
|View full text |Cite
|
Sign up to set email alerts
|

30-Year Trends in Stroke Rates and Outcome in Auckland, New Zealand (1981-2012): A Multi-Ethnic Population-Based Series of Studies

Abstract: BackgroundInsufficient data exist on population-based trends in morbidity and mortality to determine the success of prevention strategies and improvements in health care delivery in stroke. The aim of this study was to determine trends in incidence and outcome (1-year mortality, 28-day case-fatality) in relation to management and risk factors for stroke in the multi-ethnic population of Auckland, New Zealand (NZ) over 30-years.MethodsFour stroke incidence population-based register studies were undertaken in ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 87 publications
1
61
2
1
Order By: Relevance
“…Our main finding of unchanged survival appears surprising given the general decrease in stroke mortality worldwide (Feigin et al, ); however, secular trends in stroke case fatality within different populations are inconsistent, with some studies reporting decreasing fatality (Arboix et al, ; Feigin et al, ; Lee et al, ; Nimptsch & Mansky, ), while others report stable rates (Carrera et al, ; Feigin et al, ; Fuentes et al, ; Rothwell et al, ). The majority of studies on survival after stroke include nonhospitalized strokes (Feigin et al, ; Lecoffre et al, ; Lee et al, ; Numminen et al, ; Rothwell et al, ; Wieberdink et al, ), or strokes treated in hospital but not necessarily on an SU (Appelros et al, ; Arboix et al, ; Carrera et al, ; Nimptsch & Mansky, ). All of the patients in the present study received treatment on a comprehensive SU with consistent protocols, where the main treatment advance, thrombolysis, while improving outcomes for survivors, has not been shown to better survival (Wardlaw, Murray, Berge, & Zoppo, )—and this was also observed in our population by a nonsignificant HR in the adjusted Cox regression model (Supporting Information Table S1).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Our main finding of unchanged survival appears surprising given the general decrease in stroke mortality worldwide (Feigin et al, ); however, secular trends in stroke case fatality within different populations are inconsistent, with some studies reporting decreasing fatality (Arboix et al, ; Feigin et al, ; Lee et al, ; Nimptsch & Mansky, ), while others report stable rates (Carrera et al, ; Feigin et al, ; Fuentes et al, ; Rothwell et al, ). The majority of studies on survival after stroke include nonhospitalized strokes (Feigin et al, ; Lecoffre et al, ; Lee et al, ; Numminen et al, ; Rothwell et al, ; Wieberdink et al, ), or strokes treated in hospital but not necessarily on an SU (Appelros et al, ; Arboix et al, ; Carrera et al, ; Nimptsch & Mansky, ). All of the patients in the present study received treatment on a comprehensive SU with consistent protocols, where the main treatment advance, thrombolysis, while improving outcomes for survivors, has not been shown to better survival (Wardlaw, Murray, Berge, & Zoppo, )—and this was also observed in our population by a nonsignificant HR in the adjusted Cox regression model (Supporting Information Table S1).…”
Section: Discussionmentioning
confidence: 71%
“…Existing studies reporting trends in stroke risk factors or outcomes include either both hospitalized and nonhospitalized patients (Feigin et al, ; Feigin, Lawes, Bennett, Barker‐Collo, & Parag, ; Lecoffre et al, ; Lee, Shafe, & Cowie, ; Numminen, Kaste, Aho, Waltimo, & Kotila, ; Rothwell et al, ; Wieberdink, Ikram, Hofman, Koudstaal, & Breteler, ), or patients treated in hospital, but not necessarily on an SU (Appelros et al, ; Arboix et al, ; Carrera, Maeder‐Ingvar, Rossetti, Devuyst, & Bogousslavsky, ; Nimptsch & Mansky, ). Several do not examine changes in survival outcomes (Bembenek et al, ; Lecoffre et al, ; Teuschl et al, ; Wieberdink et al, ), and none of these papers report on long‐term survival.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that antipsychotics increase the risk of mortality in people with dementia . The reason that this risk might be increased in Pacific Islanders and Māori may be due to their pre‐existing increased risk of stroke and cardiovascular events; however, these factors should be controlled for in our analysis as the final model included adjustment for comorbidity. We note that antipsychotics were less likely to be dispensed to Māori and Pacific Islanders compared with NZ Europeans, and this may be due to a clinical awareness of possible higher risk.…”
Section: Discussionmentioning
confidence: 99%
“…However, these factors have not been examined in an NZ population, which has a unique demography with differing rates of risk factors in different ethnic groups. For example, Māori and Pacific Islanders living in NZ have far higher rates of chronic diseases such as diabetes, obesity, and cardiovascular disease compared with NZ Europeans, so we might expect a higher risk of death in dementia. Understanding the predictors of survival in dementia is important to NZ health care decision makers who need to plan services for people with dementia and their families.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in incidence may also be indicative of changes in demand for different healthcare services. For example, studies have shown that both stroke incidence [5] and stroke severity [6] have decreased in both men and women during recent years, and this may be an after effect of improved prevention measures.…”
Section: Introductionmentioning
confidence: 99%